(untitled) (Journal of human and social sciences, 2025)
The Kairouan School is considered one of the most influential intellectual centers that contributed significantly to the development and dissemination of Maliki jurisprudence. Its strategic geographical location made it a major hub for scholarly exchange between the Maghreb and the Mashriq, attracting students of knowledge from across the Islamic world. Many scholars traveled from Kairouan to al-Madinah al-Munawwarah to study under Imam Malik ibn Anas and later returned with his knowledge and methodology, which played a major role in spreading the Maliki school throughout North Africa and al-Andalus. Despite facing political challenges during the Aghlabid and Fatimid periods—when Maliki scholars were persecuted and their works destroyed—the Kairouan School remained a prominent center of Islamic legal thought and a cornerstone of jurisprudential scholarship in the western Islamic world.